Effectiveness of an Educational Program on Nurses Knowledge Concerning Complications Prevention of Mechanical Ventilation at Intensive Care Unit in Al- Hussain Teaching Hospital at Nassiryah City - Suaad J. Mohammed; Hiba J. Hammod (Kufa Journal for Nursing Sciences)
Objective: Assess of Knowledge nurses and the effectiveness of educational program on nurses in intensive care units to prevent the complications of mechanical ventilation and to find the relationship between such as age and years of experience in intensive care units at hospitals in Nasiriyah with knowledge of nurses.